IN VITRO SCREENING FOR ANTICHOLINESTERASE AND ANTIOXIDANT ACTIVITY OF EXTRACT OF GARCINIA ATROVIRIDIS - V, Chitra; J, Narayanan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Garcinia atroviridis belongs to the family Clusiaceae. The whole plant was dried, extracted to obtain a xanthone-rich extract. Phytochemical studies of extract showed the presence of phenols, alkaloids, steroids, resins, and saponins. Alzheimer's disease (AD) the most common form of dementia, a brain disorder which has been affecting the elderly. The natural sources such as plants are an abundant source having various medicinal properties. Methods: In the present study, G. atroviridis has been selected to test for the acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) activity by Ellman's method. The antioxidant activity has been performed by 2,2'-diphenyl-1-picrylhydrazyl radical (DPPH) assay. Results: The results showed that the extract from G. atroviridis could inhibit the activity of AchE and BuChE. The percentage inhibition of the ethanolic extract for AChE was found to be 69.4%, and ethyl acetate extract was found to be 75.6%, respectively. The percentage inhibition of the ethanolic extract for BuChE was found to be 59.4%, and ethyl acetate extract was found to be 63.2%, respectively. The IC50 values for DPPH scavenging activity were significant when compared with the standard ascorbic acid. Conclusion: The plant extract with significant antioxidant and anticholinesterase property has shown its potential to be investigated further as a therapeutic drug for AD.